2019
DOI: 10.1108/jrim-02-2018-0032
|View full text |Cite
|
Sign up to set email alerts
|

Integration of UTAUT model in internet banking adoption context

Abstract: Purpose Technology acceptance, especially internet banking adoption, has become a vital issue in the business world today. The potential of this technology is enormous. The purpose of this study is to ascertain determinants of internet banking adoption using unified theory of acceptance and use of technology (UTAUT) and electronic service (e-service) quality, which accounts for changes in user’s intention to adopt internet banking. Design/methodology/approach The authors collected data from customers of comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
108
1
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(136 citation statements)
references
References 68 publications
22
108
1
5
Order By: Relevance
“…The third and fourth constructs of UTAUT were http://mmi.fem.sumdu.edu.ua/en also significant. Results showed that social influence and facilitating condition had positive and significant influence on intention to adopt technology and in line with several previous studies (Brown et al, 2010;Ling Keong et al, 2012;Martins et al, 2014;Rahi, 2019;Venkatesh et al, 2003b;Venkatesh et al, 2012).…”
Section: Figure 3 Path Coefficients and T-valuessupporting
confidence: 91%
“…The third and fourth constructs of UTAUT were http://mmi.fem.sumdu.edu.ua/en also significant. Results showed that social influence and facilitating condition had positive and significant influence on intention to adopt technology and in line with several previous studies (Brown et al, 2010;Ling Keong et al, 2012;Martins et al, 2014;Rahi, 2019;Venkatesh et al, 2003b;Venkatesh et al, 2012).…”
Section: Figure 3 Path Coefficients and T-valuessupporting
confidence: 91%
“…MSMEs will have a firm intention to adopt a mobile accounting app if they consider that using a mobile accounting app is easy. The positive effect of effort expectancy on information technology adoption intentions has been confirmed by several studies, such as Sultana (2019), Rahi, Mustafa, Mansour, Alghizzawi, & Alnaser, (2019) and Escobar-Rodriguez & Carvajal-Trujillo, (2014). The first hypothesis of this research is: H1: MSME owners with higher effort expectancy will have a higher intention to adopt mobile accounting app Performance expectancy is the extent an individual believes that his or her task performance would be improved through the usage of particular information technology (Venkatesh et al, 2003).…”
Section: Introductionsupporting
confidence: 56%
“…For statistical analysis product indicator approach is adopted. Product indicator approach is adequate as it produce highest robustness RAHI, Othman Mansour, Alghizzawi, & Alnaser, 2019). Earlier studies have confirmed that product indicator approach revealed highest robustness (Ghani et al, 2017;Samar & Mazuri, 2019).…”
Section: Moderating Analysismentioning
confidence: 90%